Entrepreneurship Development Programme with Reference To Small Enterprises in Nepal - Karki, Bir Bahadur (Janapriya Journal of Interdisciplinary Studies, 2017)
Entrepreneurship Development Programme (EDP) is mainly focused on development, promotion and strengthening of micro, cottage and small enterprises with the technical and financial support. The rapid entry and growth of Small Enterprises (SEs) has constituted one of the most important aspects of development in Nepal. The Government of Nepal (GON), Department of Cottage and Small Industries (DCSI) and Cottage and Small Industries Development Board (CSIDB) under Ministry of Industry (MOI) are specially responsible for development of SEs. Growth rate of SEs is in increasing trends. It seemed that there is increment of about 332 number of cottage and small industries per year. On the basis of types of ownership of business firms, private firms (Sole trading concern) are increased by 264 each year between the periods of FY 1993/94 to FY 2011/12 i.e. in nineteen year time period. The result shows that 87.6 percent cottage and small industries are operated under private firms. It is seen that most of the entrepreneurs want to be self-employees and / or want to work independently. Out of five development regions, central development region has got highest position in the context of increase number of SEs as well as high increment i.e. 658 in each year. Out of total cottage and small industries, near about half i.e. 47.78 percent industries are conducted in central development region. Janapriya Journal of Interdisciplinary Studies, Vol. III (December 2014), page: 16-22